PENGARUH PELATIHAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Putri Aldina Rahmawati; Samsuri Samsuri; Ismartaya (Fakultas Ekonomi Universitas Djuanda, 2023)
The aim of the research is to find analysis and influence between training, motivation, work environment and performance and can be used as a reference for further research. The chosen method is multiple linear regression analysis. The total sample of the entire work is 49 people. The results of the study simultaneously all variables affect employee performance. Partially, training and environmental variables have an effect on employee performance, while motivational variables have no effect on employee performance. Motivational training and work environment each have an important role in improving employee performance.